To be or not to be nas malhas híbridas do suporte digital YouTube: Práticas de leitura, linguagens e o sujeito - Pimenta, Leny André [UNESP]; Momesso, Maria Regina [UNESP]; Assolini, Filomena Elaine Paiva (Universidade Estadual de Maringa, 2016)
The article observes and ponders on the reading practices of an animated short film scene of To be or not To be of Hamlet in digital support YouTube. Given the premise that support change can promote changes in reading procedures and, consequently, produce effects of meaning that reverberate in the structure of the discursive subjects involved in the process of construction of literary art, especially in the authorship. Reflection is based on discourse analysis of French 'line' and Lacanian Psychoanalysis, in which postulates deal with the historical determination of meaning processes, considering that the meanings are constructed as singular, in the relationship with the other and in their environment, and, for that, the subject has to take possession of the language field. Based on these assumptions, the corpus is configured by the virtual narrative of the animated short film Mabinogi: Hamlet - To be, or not to be, Scene One, which makes a clipping of a classic literary Shakespeare's work, Hamlet. The results point to multiple, hybrid reading gestures, in which senses and possibilities for co-Authoring can reverberate in the work of the adolescent that is constituted through language and questioning about his own self.
Into the hybrid net of youtube as support of reading: Reading practices, languages and subject
Keywords: Languages; Reading practices; Speech analysis